Small Intestinal Bacterial Overgrowth in Children with Short Bowel Syndrome. - DeGonza, Hannah; Pham, Thu Anh; Elmaoued, Rasha; Alkhouri, Razan; Castillo, Ricardo Orlando; Dharmaraj, Rajmohan (Children, 2025)
Small Intestinal Bacterial Overgrowth (SIBO) is characterized by an abnormal proliferation of bacteria in the small intestine, leading to gastrointestinal symptoms and nutritional deficiencies. Short Bowel Syndrome (SBS), resulting from extensive surgical resection of the small intestine, predisposes children to SIBO due to anatomical disruptions, motility dysfunction, parenteral nutrition dependence, and immune dysregulation. Clinical manifestations of SIBO in SBS include bloating, diarrhea, malabsorption, and failure to thrive, with severe cases leading to complications such as D-lactic acidosis. Diagnosis remains challenging, with breath testing being the most commonly used method despite limitations in accuracy, especially in SBS patients. Jejunal aspiration, the gold standard, presents limitations due to contamination risks, potential for sampling error, and a relatively low diagnostic yield. Management involves antibiotics like rifaximin and metronidazole, alongside strategies to address anatomical dysfunction, optimize nutrition, and prevent recurrence. Adjunctive therapies, including probiotics and dietary modifications, show promise but require further validation in children. Emerging treatments, such as glucagon-like peptide-2 (GLP-2) analogs, may enhance mucosal integrity and reduce SIBO risk. Given the chronic and recurrent nature of SIBO in SBS, a multidisciplinary approach is essential, integrating gastroenterological, surgical, and nutritional care to effectively manage the condition. Future research should focus on improving diagnostic methods, refining treatment protocols, and exploring targeted therapies to enhance outcomes and quality of life for affected children.